2020
DOI: 10.46413/boneyusbad.774824
|View full text |Cite
|
Sign up to set email alerts
|

Üniversite Öğrencilerinin E-Sağlık Okuryazarlık Düzeylerinin Karşılaştırılması: Sağlık Bilimleri Lisans ve Lisansüstü Öğrencileri Üzerine Bir Araştırma

Abstract: Amaç: İnternet, genç bireyler arasında kullanımı yaygın bir araçtır. Bu araştırmada interneti yoğun olarak kullanan üniversite öğrencilerinin bu alanda geliştirmiş oldukları yetkinliklerin demografik veriler kapsamında incelenmesi ve farklılıkların tespit edilerek nereden kaynaklandığının ortaya koyulması amacı ile planlanmıştır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…In the study, no significant difference was found between health literacy levels and age, gender, average annual visits to healthcare facilities, and daily internet usage. However, Norgaard et al, 17 Deniz, 18 Uslu and Şeremet, 19 Aktürk, 20 Orhan et al, 22 and Hoşgör and Tosun, 23 observed differences in their studies.…”
Section: Discussionmentioning
confidence: 96%
“…In the study, no significant difference was found between health literacy levels and age, gender, average annual visits to healthcare facilities, and daily internet usage. However, Norgaard et al, 17 Deniz, 18 Uslu and Şeremet, 19 Aktürk, 20 Orhan et al, 22 and Hoşgör and Tosun, 23 observed differences in their studies.…”
Section: Discussionmentioning
confidence: 96%
“…The health sector has also been seriously affected by these transformations, and new formations have been experienced in the sector. The internet is now a very powerful platform for us to access not only important and rare health information but also health information on the other side of the world instantly (Orhan et al, 2020). In this context, ehealth has become a part of our lives in both language and practice since the 2000s.…”
Section: E-health Literacymentioning
confidence: 99%